Defect Estimation of Steel Fiber Reinforced Concrete Members Using the Impact Echo Method - Hong, Seonguk; Kim, Jonghyun; Kim, Seunghun (International Journal of Engineering and Technology, 2019)
Among fiber-reinforced composites, steel fiber strengthens concrete and makes up for brittleness, which is a weakness of the concrete material. For this reason, steel fiber is used to reduce the weight of concrete in order to enhance its strength. While it is a recent trend to use steel fiber reinforced concrete for silos, tunnels, etc., there are few studies on its quality management and applicability assessment. This study applies the non-destructive inspection method, which is a quality management instrument, to assess the quality management and applicability of steel fiber reinforced concrete. This study verifies the possibility and reliability of steel fiber reinforced concrete quality management by means of nondestructive test methods. In this experiment, the specimens are hollow column members with thicknesses of 100 mm, 150 mm and 200 mm and slab members with defect parameters of 120 mm, 200 mm and 240 mm. As 9 variables were applied to the experiment where hollow column members were used, the error rate of specimens whose design strength was 24 MPa was 4.0%, that of specimens whose design strength was 30 MPa 2.6%, and that of specimens whose design strength was 40 MPa 1.8%, respectively. As for specimens with defects inside, the error rate was 6.9%, 4.1%, and 3.7%, respectively. The average error rate of these was 3.8%, which indicates a relatively high level of reliability.Â Â